Association of LPIN1 gene variations with markers of metabolic syndrome in population from Bosnia and Herzegovina - Tamer Bego; Tanja Dujić; Barbara Mlinar; Sabina Semiz; Maja Malenica; Besim Prnjavorac; Barbara Ostanek; Janja Marc; Anida Čaušević-Ramoševac; Adlija Čaušević (Medicinski glasnik, 2015)
Aim: To investigate association of two LPIN1 gene variations with main traits of metabolic syndrome (MS) (waist circumference, body mass index, blood pressure, triglycerides, HDL-cholesterol and fasting glucose levels) in population from Bosnia and Herzegovina. Methods: This study included 43 patients with metabolic syndrome and 43 healthy controls from General Hospital in Tešanj, Bosnia and Herzegovina. Subjects were genotyped for two LPIN1 gene variations (rs11693809: C>T and rs2716610: C>T) by real time PCR method. Results: In control subjects LPIN1 polymorphism, rs2716610: C>T, was significantly associated with a lower body mass index (BMI) (p=0.008) and waist circumference (p=0.008). The second analyzed rs11693809: C>T polymorphism was associated with lower blood HbA1c levels (p=0.048) in a group of MS patients. Conclusion: Results: of our study suggest that rs2716610: C>T polymorphism of LPIN1 gene could have a protective effect against development of metabolic syndrome, while rs11693809: C>T might affect a glucose control in patients with MS.
Keywords: metabolic syndrome; LPIN1 gene; markers; gene variations.